2013
DOI: 10.1007/s00253-013-4970-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Clostridium butyricum and Enterococcus faecium on growth performance, lipid metabolism, and cecal microbiota of broiler chickens

Abstract: To investigate the effects of Clostridium butyricum and Enterococcus faecium on the growth performance, lipid metabolism, and cecal microbiota of broilers, 264 one-day-old male Ross 308 broiler chicks were randomly allocated into four treatments with six replicates in a 2 × 2 factorial arrangement and fed four diets with two levels of C. butyricum (0 or 1 × 10⁹ cfu/kg) and two levels of E. faecium (0 or 2 × 10⁹ cfu/kg) for 42 days. There was no significant interaction between C. butyricum and E. faecium on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 58 publications
4
71
0
Order By: Relevance
“…PPAR-γ is expressed at the highest level in adipose tissue and promotes adipocyte differentiation (Mandrup and Lane, 1997), and its expression did not change after adding FCSM in the broiler chickens' diet. LPL, a critical enzyme in the hydrolysis of TG, catalyzes TG from circulating chylomicrons and very-low-density lipoprotein in adipose tissue (Zhao et al, 2013). In the present study, the down-regulated mRNA level of LPL in abdominal fat was associated with a decreased fatty acid synthesis, hepatic TG content, and fat deposition in abdominal fat in the chickens fed the diet containing FCSM.…”
Section: Discussionsupporting
confidence: 55%
“…PPAR-γ is expressed at the highest level in adipose tissue and promotes adipocyte differentiation (Mandrup and Lane, 1997), and its expression did not change after adding FCSM in the broiler chickens' diet. LPL, a critical enzyme in the hydrolysis of TG, catalyzes TG from circulating chylomicrons and very-low-density lipoprotein in adipose tissue (Zhao et al, 2013). In the present study, the down-regulated mRNA level of LPL in abdominal fat was associated with a decreased fatty acid synthesis, hepatic TG content, and fat deposition in abdominal fat in the chickens fed the diet containing FCSM.…”
Section: Discussionsupporting
confidence: 55%
“…Barter et al (2010) reported that a link may exist between the changes in HDL-C and TG, but they found no apparent relationship between LDL-C reduction and HDL-C increase. However, Zhang et al (2011) and Zhao et al (2013) observed that diet containing Clostridium butyricum and Enterococcus faecium exerted no effect on the concentrations of TG, TC, HDL-C, and LDL-C in broiler sera. Meanwhile, the serum INS levels were enhanced by C .…”
Section: Discussionmentioning
confidence: 98%
“…PPAR-α, as a member of nuclear receptors, is highly expressed in the liver and plays an important role in regulating glucose and lipid metabolism or enhancing the related-gene expression in fatty acid oxidation (Lee et al, 1995;Zhang et al, 2011;Huang et al, 2013). LPL, on the other hand, catalyzes triglycerides from circulating chylomicron and very low-density lipoprotein to generate fatty acids and glycerol for tissue utilization or storage (Zhao et al, 2013). Again, this time due to the different changes in the PPAR-α and LPL expression levels in the liver tissue, there was a distinction between CSM fermented by C. tropicalis and CSM fermented by C. tropicalis plus S. cerevisiae.…”
Section: Effect Of Cottonseed Meal Fermented With Yeast On the Lipid-mentioning
confidence: 99%
“…Moreover, Zhao et al (2013) reported that probiotics (Clostridium butyricum and Enterococcus faecium) enhance the mRNA abundance of lipogenic genes in male broilers, including ACC, FAS, and malic enzyme in the liver tissue. However, in the present study, the expressions of FAS and L-FABP in the liver tissue were not altered and, therefore, do not agree with the results of Zhao et al (2013). These differences may be attributed to differences in yeast strain, broiler breed, and feeding system.…”
Section: Effect Of Cottonseed Meal Fermented With Yeast On the Lipid-mentioning
confidence: 99%